Molecular tilt angle and order parameter of low molar mass ferroelectric liquid crystal using IR spectroscopy - VIJ, JAGDISH KUMAR; PEROVA, TANIA (My University, 1996)
Fourier transform infrared spectroscopy of a ferroelectric liquid-crystalline material: 4-(3)-(S)- methyl-2-(S)-chloropentanoyloxy-4'-octyloxy-biphenyl has been investigated in the wavenumber range 450 - 4000 cm-1 for various temperatures and as a function of direct bias voltage in its SmC* phase. Samples prepared in both homeotropic and homogeneous alignments have been studied. The order parameter was calculated for several isolated IR vibrations which are characteristic of different parts and orientations of molecules. The dependence of the molecular tilt angle on direct bias voltage and temperature has similar characteristics to those obtained from electro-optic measurements.
PUBLISHED
Keywords: Mechanical and Manufacturing Engineering